Sports science research and technology support : second international congress, icSPORTS 2014, Rome, Italy, October 24-26, 2014 : revised selected papers /: second international congress, icSPORTS 2014, Rome, Italy, October 24-26, 2014 : revised selected papers. (2015) - Unknown
No abstract available